Media Choice and the Polarization of Public Opinion About Covid-19 in Brazil - Batista Pereira, Frederico; Nunes, Felipe (Revista Latinoamericana de Opinión Pública, 2021)
Brazil is one of the countries most affected by the Covid-19 pandemic. Yet, while rates of contagion and deaths increase over time, polls show that opinions about the pandemic become less concerned about the virus and less supportive of mitigation measures. According to observers, a key factor in this process is President Bolsonaro’s denialist stance. In this paper, we show that patterns of media choice help explain how Bolsonaro influences public opinion over time. Using three online surveys conducted at different stages of the pandemic, we show that the divergence in views about the pandemic is driven largely by Bolsonaro supporters who prefer to consume news online. The findings have implications not just for understanding the politicization of the pandemic in Brazil, but also for the relationship between populism and mass communications in the social media era.